Village ecosystem vulnerability in karst desertification control: evidence from South China Karst - Tang, Jiuhan; Xiong, Kangning; Wang, Qi; Chen, Yue; Wu, Qinglin (Frontiers in Ecology and Evolution, 2023)
Against the background of global environmental changes and the intensification of human activity, the village ecosystem faces enormous challenges. In particular, the rural areas in South China Karst face serious problems, such as karst desertification and human–land conflicts. In recent decades, the Chinese government and scientific researchers have committed to controlling karst desertification. However, village ecosystems in the context of karst desertification control (KDC) remain fragile. To promote the sustainable development of villages in KDC, this study considered village ecosystems in different karst desertification areas as study cases. Based on the model of susceptibility-exposure-lack of resilience, we constructed an index system of vulnerability research, used the entropy method to determine the weight, and introduced a contribution model to clarify the vulnerability level and vulnerability driving factors to recommend related governance strategies. We found that (1) the village ecosystem vulnerability levels under KDC were different. Village ecosystems were mildly vulnerable in none-potential KDC areas, moderately vulnerable in potential-mild areas, and moderately and highly vulnerable in moderate–severe KDC areas. (2) The combined effects of the natural environment and human activity have led to the vulnerability of village ecosystems in KDC in South China Karst. Among them, topography, climate, forest coverage, landscape pattern, soil erosion, karst desertification, economic development level, and production and living activity are the main factors affecting the village ecosystem vulnerability of KDC in South China Karst, and the differences in these factors lead to differences in vulnerability levels of different village ecosystems. (3) We designed adaptive governance strategies for village ecosystems based on the factors influencing the characteristics and vulnerability of different karst desertification areas, with the primary goal of sustainable development. They provide a decision-making basis for promoting sustainable development of the village ecosystems in KDC.